EFL LEARNERS’ PERSPECTIVES TOWARDS THE USE OF EDMODO IN THE TEACHING AND LEARNING OF TRANSLATION SUBJECT - Gesy Gania (Journal of English Education Program (JEEP), 2020)
This study is about the use of Edmodo in the teaching and learning of Translation Subject. This study was aimed at investigating the EFL learners' perspectives towards the use of Edmodo in the teaching and learning of Translation Subject and finding out the EFL learners' perspectives on the advantages and disadvantages of the use of Edmodo. This study employed qualitative method with survey design. This study involved 48 participants at fourth-year students of English Department in two universities. The data were collected from closed-ended questionnaire and interview. Based on the result close-ended questionnaire the researcher concluded that the students gave positive perspectives about the use of Edmodo in the teaching and learning of Translation Subject, they assumed that the use of Edmodo in the teaching and learning of Translation Subject really helps them to do some tasks from the lecturer easily and can be implemented anytime and anywhere. From the interview the researchers concluded the advantages that Edmodo helped the users to do the task or share the information, not consuming the time, and they could learn anywhere anytime and not paper consuming. Futhermore, the disadvantages of Edmodo, that Edmodo it’s not too effective for teaching and learning process in Translation Subject. In conclusion, Edmodo will be efficient to access when they have good internet connections. But, Edmodo it’s not too effective for teaching and learning process in Translation Subject because when the teacher gives the materials without explanation, the students will get confused. Finally, this study suggest other researcher to use the results of the study to give more objective data, from many instruments to enrich their research, extend the sample of the study and employ other method and design in order to enrich the data.Keywords: Edmodo, teaching and learning process, Translation Subject